(untitled) (Journal of Hama University, 2022)
The research was conducted on 120 birds of strain (ROSS 308) with a similar weight and age one day and unsexed in order to study the effect of different concentrations of the powder of the olive leaf on some productivity indicators in broilers such as feed consumption rate and live weight and feed conversion factor. were distributed birds randomly into four groups of 30 birds each group and each group containing three replicates and were given a standard diet to the first group (control), while dry matter was added to the olive leaf concentrations (1-2-3) %/ kg respectively to a standard diet, the experiment lasted for 42 days. The results of the experiment showed that the addition of olive leaf for the standard diet for broiler led to an increase significantly (P <0,05) in the rate of feed consumption, especially in the second group and the fourth when compared with the control group. The 4th group 3 % / kg) outperformed significantly in the cumulative rate of feed consumption by the end of the experiment, recorded 4773.11 g, while the control group was recorded 4435.60 g. In terms of live weight third group showed a significant decrease (P<0,05) where it recorded the weight of 2497.20g. the rest of the groups was similar to the control group which scored 2586.96 g. With regard to the feed conversion factor, the second and third group showed a clear improvement clearly in the first four weeks, but in the last two weeks the experience groups did not show any improvement in the feed conversion factor. This study concludes that the addition of powder of olive leaves to the standard diet for broiler led to a clear improvement in production indicators in only the first four weeks.